The Impact of the Civil Rights Movement on Educational Segregation in the United States - Robinson, Emily (European Journal of Historical Research, 2024)
Purpose: the aim of the study was to investigate the impact of the civil rights movement on educational segregation in the united states Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The findings reveal three notable research gaps. Firstly, while the analysis provides a comprehensive view of the Civil Rights Movement's objectives and impact on educational segregation, a conceptual gap exists in the lack of in-depth exploration into the precise mechanisms through which the movement's strategies translated into concrete changes within educational policies and practices, necessitating a more nuanced understanding of these linkages. Secondly, a contextual gap emerges as the study outlines distinct Civil Rights Movements and their implications for educational segregation, yet lacks an investigation into the interplay between these movements and the broader socio-political context that shaped their strategies and outcomes. Unique Contribution to Theory, Practice and Policy: Social identity theory and critical race theory may be use to anchor future studies on the impact of the civil rights movement on educational segregation in the united states. Promote culturally relevant teaching practices that acknowledge and incorporate diverse cultural perspectives into the curriculum. Diversity in School Governance: Encourage policies that promote diverse representation in school boards, administrative leadership, and decision-making bodies.